EU state aid decisions and innovative SMEs - Kurtovič, Vedad (2018)
Purpose of this work is to shed more light on financial issues Small and Medium Enterprises face when engaging in innovative processes. European Union plans to foster more growth and innovation in its Europe 2020 agenda, where it plans to address issues related to Research and Development in order to make the region more competitive in global markets. This work takes form of an empirical literature survey and focuses on three main outputs that are achieved through state aid for Research and Development: employment, productivity and performance and innovation. It shows positive impact of state aid support and that they increase employment, increase sales and innovative sales, the effect on these sales lingers for several years, helps companies increase their innovation capacities in more than 50 % of firms and that these Research and Development grants have a larger impact for smaller firms.